Review of the Hemiosus Sharp and Derallus Sharp of North America, Central America, and the Caribbean (Coleoptera: Hydrophilidae: Berosini) - Short, Andrew Edward Z.; Torres, Phillip J. (Zootaxa, 2006)
Species of the New World genera Hemiosus Sharp and Derallus Sharp that occur outside continental South America are reviewed; three and five species are recorded respectively. Hemiosus selva Short, sp. n. is described from Costa Rica. Hemiosus toxillus d’Orchymont is a junior synonym of H. exilis (LeConte). A key to the genera of Berosini and the species of Derallus and Hemiosus occurring outside South America is presented with diagnostic features illustrated. New locality records are provided for all species.